Hashtagging "Good" Muslim Performances Online. Issue 2 (2nd April 2020) - Selby, Jennifer A.; Funk, Cory
ABSTRACT: This paper examines a "Muslim twist" used to signal inoffensiveness by our Muslim Canadian interlocutors in their use of hashtags online. We consider and critique this "twist" observed in our qualitative data of a seeming juxtaposition of a Muslim-related term with a seemingly non-Muslim object or emotion. Based on discursive analysis of our interlocutors' description of their hashtag usage, we situate this phenomenon in a context of rising securitization and the individualization afforded by social media. We argue that "Muslim twist" hashtags mobilize their polysemic and viral nature to both perform and interrupt normative online sensibilities in ways that reveal continuing burdens of "good Muslim" public performances, now online.